Extraction of volatile oils and evaluation some features of volatile oil from the leaves of some local Eucalyptus spp trees and comparing them with volatile oil of some foreign species - Thuraya A . Abbas; Hala M . Musbah (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
This study included the extraction of volatile oils from the leaves of some local Eucalyptus trees (i.e.(1)E.camldulensis ,(2) E.camldulensis , E.microtheca , E.globules , E.sideroxylem , E.krusianin. by the water distillation method. As well as exploring some of their physical properties.       The results of this study reveald that the local eucalyptus trees gave a good rate of volatile oil equals to some global kinds and to the rate in India pharmacopeia.       Also the results revealed that there had been concurrence between the percentages of volatile oils and refractive index and specific gravity of the plants on which the study was made to study and those included in the US and UK. pharma copeias. This proves those plant , are of medical importance.